Effects of Tea Fixation Methods and Fermentation Time on Total Phenol, Caffeine Content, and Consumer Acceptance of Kombucha Tea - Cici Mahmuda; Pudji Astuti (Universitas Negeri Padang, 2026)
Serious health problems such as the risk of prediabetes, decreased immune function, hypertension, and digestive disorders are increasing among young people. This condition has increased public awareness of maintaining health. In response, various foods and beverages that support health have emerged, including green tea and its derivative product, kombucha tea, which can be an alternative to address these health issues. This study investigated kombucha tea produced using different fixation methods (panning and steaming) and fermentation durations (7 and 10 days) on total phenolic content, caffeine content, and consumer preference. The analysis of total phenolic content and caffeine content employed a quantitative approach using an experimental method with a 2×2 factorial design and three replications. The research process included tea production using panning and steaming methods, followed by fermentation with starter culture and SCOBY for 7 and 10 days. Chemical analyses were then conducted to determine total phenolic and caffeine contents, along with a hedonic test using a 9-point scale. Data were analyzed using Two-Way ANOVA followed by Tukey’s test for total phenolic and caffeine contents, while non-parametric Kruskal–Wallis and Mann–Whitney tests were used for hedonic data analysis. The results showed that the highest total phenolic content (1191.56 ppm) was obtained from steaming with 10 days of fermentation, while the lowest (677.22 ppm) was found in panning with 10 days of fermentation. The highest caffeine content (189.23 ppm) was observed in steaming with 7 days of fermentation, while the lowest (53.93 ppm) was found in steaming with 10 days of fermentation. The interaction between fixation method and fermentation duration (p < 0.05) significantly affected total phenolic content, caffeine content, and consumer preference. The steaming treatment with 10 days of fermentation produced the highest total phenolic content (1191.56 ppm) and the lowest caffeine content (53.93 ppm); however, the 7-day fermentation treatment was preferred by the panelists. Total phenolic and caffeine contents did not significantly affect sensory attributes and therefore did not influence consumer preference.